(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to examine the psychological development of preschool children from the perspective of kindergarten teachers in Iraq. The researcher developed a psychological development scale, which consists of 20 items in its final version. The scale was validated for content validity and construct validity. The researcher also tested the reliability using the test-retest method, with a sample of 40 children (both male and female), with their responses being provided by their kindergarten teacher. The Cronbach’s alpha coefficient for reliability was found to be 0.72. The research tool was applied to a sample of 150 kindergarten teachers from public kindergartens, selected purposively.The research results indicated that the sample exhibited psychological development, and it also revealed that there were no statistically significant differences between male and female participants in the study in relation to the research variables. Conclusions: The sample of preschool children possesses a high level of psychological development. There are no statistically significant differences in the level of psychological development based on gender, meaning both male and female children in the sample exhibit a similar level of psychological development. Recommendations: Incorporate activities that foster psychological development into the daily curriculum. Provide regular psychological development assessment programs for preschool children. Suggestions: Measure psychological development in preschool children based on modern developmental standards. Conduct comparative studies between public and private kindergartens or between urban and rural environments. Conduct studies measuring various aspects of development based on other variables (e.g., blood type, genetic diseases, parental academic level, etc.).